2017
DOI: 10.1038/srep40868
|View full text |Cite
|
Sign up to set email alerts
|

Significantly enhanced osteoblast response to nano-grained pure tantalum

Abstract: Tantalum (Ta) metal is receiving increasing interest as biomaterial for load-bearing orthopedic applications and the synthetic properties of Ta can be tailored by altering its grain structures. This study evaluates the capability of sliding friction treatment (SFT) technique to modulate the comprehensive performances of pure Ta. Specifically, novel nanocrystalline (NC) surface with extremely small grains (average grain size of ≤20 nm) was fabricated on conventional coarse-grained (CG) Ta by SFT. It shows that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 52 publications
4
34
0
Order By: Relevance
“…33 In addition, a nanocrystalline Ta surface possessed higher surface hydrophilicity and enhanced corrosion resistance than those of conventional coarse-grained Ta. 34 Therefore, it was interesting to study how uncombined Ta nanoparticles behave. In the present study, MC3T3-E1 osteoblasts were cultured with 1, 10, and 20 μg/mL uncombined Ta-NPs, revealing that the cell viability increased compared with that of the untreated group, indicating that Ta-NPs can also promote osteoblast proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…33 In addition, a nanocrystalline Ta surface possessed higher surface hydrophilicity and enhanced corrosion resistance than those of conventional coarse-grained Ta. 34 Therefore, it was interesting to study how uncombined Ta nanoparticles behave. In the present study, MC3T3-E1 osteoblasts were cultured with 1, 10, and 20 μg/mL uncombined Ta-NPs, revealing that the cell viability increased compared with that of the untreated group, indicating that Ta-NPs can also promote osteoblast proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, tantalum has received a considerable amount of attention regarding its application in the biomedical sector. The metal was known to exhibit good biocompatibility since the 1940s [ 1 , 2 , 3 ]. However, its high cost and density explain why it has not been researched as vigorously as titanium and its alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Results have shown that cellular responses often depend on the mechanical properties, pattern structures, and surface chemistry of the microenvironment surrounding the cells [1,3,4,5,7,8,10,11,12,13,14,15,16,17,18,19,20]; however, work done thus far has been conducted with structures composed of monolithic materials having uniform surface chemical composition. Studies of cell behavior on nanocomposite surfaces are limited [1,3,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%